PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA INVENTORY BERBASIS WEB DI PT. EXPRESSA PARIWARA MEDIA - Rio Pratama; Saprudin (LOGIC : Jurnal Ilmu Komputer dan Pendidikan, 2023)
PT. Expressa Pariwara Media is an Electronic provider company, but so far data processing from the warehouse admin cannot be updated online and is computerized so that it cannot be accessed outside the office, as technology develops, Microsoft Excel is no longer the official data collection medium for companies of the same class as a Limited Liability Company. Currently PT. Expressa Pariwara Media only relies on general ledger-based data collection and also Microsoft Excel, which often delays updating incoming and outgoing data. So that by making this website-based data collection, it can shorten the time to search for data on goods and also the stock of goods in the company without having to go to the office and can be accessed on various gadgets anywhere. Qualitative Research Methods Data Collection Methods Collecting data in direct observation, namely at PT. Expressa Pariwara Media and collect additional data with literature study. System Development Method The method used in this research is the Waterfall method. The Waterfall model has a process that flows systematically from one stage to another. These stages are analysis, design, coding, testing, maintenance. by creating an online inventory system, PT Expressa advertising media can produce more effective and efficient performance so as to make the company more advanced in the process of recording goods warehouses based on the results of research and discussion at PT. Expressa Pariwara Media, this system can be interpreted that: With an online and computer system that is structured in data-inventory processing, it can facilitate online performance and minimize the occurrence of errors or delays in performance for employees at PT. Expressa Advertising Media. With an information system for processing incoming and outgoing goods data online, it can minimize errors in processing goods. By using a computerized system, online report processing is faster, more precise and accurate.